The Effect of Using Google Translate on English Verb Pronunciation of Grade, I Students at Saengtham Wittaya Foundation School, Chana-Songkhla - Novyola Cindy Afrina; Khairunnisah; Ayunda Sabrina Sormin; Lili Herawati Parapat (Universitas Islam Negeri Palopo, 2026)
This quantitative research aimed to investigate the effect of using Google Translate on English verb pronunciation among Grade I students at Saengtham Wittaya Foundation School in Chana-Songkhla. The study employed a pre-experimental design with a one-group pretest-posttest approach. A sample of 30 Grade I students participated in the study during the academic year. The research instruments included a pronunciation test administered before and after the intervention. Students used Google Translate as a learning tool to practice English verb pronunciation over a period of instruction. Data were analyzed using descriptive statistics and paired sample t-test to determine the significant difference between pretest and posttest scores. The findings revealed that students' English verb pronunciation improved significantly after using Google Translate as a supplementary learning tool. The mean score increased from the pretest to the posttest, indicating positive effects of technology integration in pronunciation instruction. This study provides evidence for educators regarding the potential benefits of incorporating Google Translate in teaching English pronunciation to young learners.